2011
DOI: 10.3109/08923973.2011.608360
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative description of the peptide sharing between poliovirus andHomo sapiens

Abstract: In the present study, we analyze the peptide commonality between poliovirus polyprotein and the human proteins. We report on the following findings: (1) the extent of polio peptide overlap on the human proteome is high, and involves the entire viral polyprotein; (2) viral peptide matching affects human proteins linked to fundamental cellular functions. The data may help to further our understanding of the relationships between poliovirus and the human host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(71 reference statements)
1
6
0
Order By: Relevance
“…In conclusion, the present study confirmed and extended previous reports from this laboratory and others presenting evidence for a massive peptide overlap between viral and human proteomes. Having as a reference frame such a corpus of data, here we detailed the peptide commonality between WNV and the human proteome.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, the present study confirmed and extended previous reports from this laboratory and others presenting evidence for a massive peptide overlap between viral and human proteomes. Having as a reference frame such a corpus of data, here we detailed the peptide commonality between WNV and the human proteome.…”
Section: Discussionsupporting
confidence: 92%
“…In this scenario, new vaccine formulations and renewed research efforts might help to specifically fight PV infection. Recently, we analyzed the peptide overlap between PV1, strain Mahoney, and the human proteome and described a high extent of peptide sharing involving human proteins linked to fundamental cellular functions [ 9 ]. These data appeared to be of interest also because PV has been studied mainly at the nucleotide level [ 10 ], and, in general, there is a lack of knowledge of the interaction(s) between PV and the human host at the peptide/protein level.…”
Section: Introductionmentioning
confidence: 99%
“…Following the mathematical quantification of pentapeptide sharing between PV1 and human proteins, we reported that 2,040 out of the 2,204 pentamers composing the PV1 proteome are shared with the human proteome for a total of 18,223 matches, including multiple occurrences [ 9 ]. In general, a vast peptide sharing with human proteins is a characteristic of viral proteomes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial proteomes massively overlap human proteins [34][35][36][68][69][70] in a tight network of metabolic interactions that may carry pathologic sequelae in the host. Indeed, bacterial organisms may interfere with the apoptotic apparatus [71], manipulate and subvert host-cell pathways [72], and interfere with the host immune system and mechanisms [73].…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%